Audit Committee and Discretionary Loan Loss Provisions in Tunisian Commercial Banks - Zgarni, Amina; Fedhila, Hassouna; El Gaied, Moez (International Journal of Economics and Financial Issues, 2018)
The purpose of this paper is to study the effect of the audit committee (presence, expertise, independence, size and activity) on earnings management of Tunisian commercial banks. We selected a sample of ten Tunisian commercial banks examined over the 2001 to 2014 period. The regression models are estimated using the “Panel Corrected Standard Errors” method of Beck and Katz (1995). Our empirical results highlight the effective role of the audit committee’s expertise in mitigating discretionary practices. However, the number of meetings, which is less than the standard required by regulatory authorities, does not have a significant disciplinary effect on earnings management practices. Results also report that Audit committee’s independence and size have positive effects on earnings management in our sample. Keywords: audit committee, earnings management, discretionary loan loss provisions. JEL Classifications: G14, M4, M41